Ethnic diversity outpatient clinic in paediatrics - Dahhan Nordin; Meijssen Dominique; Chegary Malika; Bosman Diederik; Wolf Bart (BMC, 2012)
Abstract Background The health status of chronic sick ethnic minority children in the Netherlands is unequal compared with indigenous Dutch children. In order to optimize the health care for these children a specific patient-oriented clinic in ethnic-cultural diversity: the Mosaic Outpatient Clinic (MOC) was integrated in the general Paediatric Outpatient Departments (POPD) of three hospitals in Amsterdam. Methods Feasibility of the MOC, factors influencing the health care process and encountered bottlenecks in health care were studied in ethnic minority children with asthma, diabetes type 1 or metabolic disease originating from Morocco, Turkey and Surinam. Feasibility was determined by the number of patients attended, support from the paediatric medical staff and willingness of the patients to participate. Influences on the health care process comprised parents' level of knowledge of disease, sense of disease severity, level of effort, linguistic skills, health literacy, adherence to treatment and encountered bottlenecks in the health care process. Moreover, the number of admissions and visits to the POPD in the years before, during and after the MOC were analysed. Results In 2006 a total of 189 ethnic minority children were seen. Integration of the MOC within the general POPD of the hospital is feasible. The ability of the parents to speak and understand Dutch was found to be 58%, functional health literacy was 88%; sufficient knowledge of disease and sense of disease severity were 59% and 67%, respectively. The main bottlenecks in the healthcare process: poor knowledge of disease, limited sense of disease severity and low health literacy in the parents proved to be the best predictors for decreased adherence. After attending the MOC there was a decrease in the number of admissions and visits to the POPD for asthma while the number of visits increased in patients with diabetes and the amount of no-shows decreased in patients with a metabolic disease. Conclusion Integration of a MOC in the general POPD is feasible and appreciated by the parents, provides more insight in the problems ethnic minority children and their parents face and shows promising directions for optimizing adherence in these children.